Intraoperative Thermal Imaging for Evaluating Blood Perfusion During Laparoscopic Colorectal Surgery. Issue 3 (June 2021) - Tokunaga, Takuya; Shimada, Mitsuo; Higashijima, Jun; Yoshikawa, Kozo; Nishi, Masaaki; Kashihara, Hideya; Takasu, Chie; Ishikawa, Daichi; Yoshimoto, Toshiaki
Abstract : Background: Anastomotic leakage is a feared complication of anterior resection for rectal cancer. Among the various factors reported to be involved in the occurrence of anastomotic leakage, blood perfusion of the remnant intestine is one of the most important. Recently, the usefulness of evaluating blood perfusion using indocyanine green (ICG) has been reported. We therefore aimed to show that measuring intestinal temperature using thermography is useful for evaluating blood perfusion. The authors also investigated the relation between intestinal temperatures and the ICG fluorescence time (FT). Materials and Methods: Altogether, 45 patients who underwent laparoscopic anterior resection for rectal cancer between July 2017 and September 2018 were enrolled in this study. ICG FT and intestinal temperature were measured after the mesenteric dissection. Result: The temperature boundary could be easily identified using thermographic images. The temperature of the residual intestinal tract was significantly higher than that of the resected intestinal tract at the planned separation line (29.9 vs. 27.3°C). In addition, there was an inverse correlation between the ICG FT and the temperature of the residual intestine. Conclusion: Intestinal temperature measurement through thermography is a useful new tool for evaluating intestinal blood perfusion.